ANALISIS PUTUSAN PERKARA PIDANA NO / 52 / PID.SUS – TPK / 2019 / PN. MKS TENTANG TINDAK PIDANA KORUPSI: DECISION ANALYSIS OF CRIMINAL CASE NO / 52 / PID.SUS – TPK / 2019 / PN. MKS CONCERNING CRIMINAL ACTS OF CORRUPTION - Yustika, Mayang; Mas, Marwan; Zubaidah, Siti (Faculty Of Law Bosowa University, 2021)
Thisaresearch aims to find out how the application of elements of corruption crimes and to know the basis of consideration of judges in deciding the case No:52/Pid.Sus-TPK/2019/PN.Mks. Thisaresearch was conducteda in makassar districtacourt using Normative research method using data collection techniques through interviews, literature studies, and documents. After analyzing the data obtained from the results of the study, the authors used qualitative approach data analysis techniques, which is a research procedure that produces descriptive data. Based on the results of the study the author can conclude that the application of criminal law elements in the corruption of the Village Fund in the verdict No: 52/Pid.Sus-TPK/2019/Pn.Mks has been in accordance with the subsidair indictment chosenaby the Panel of Judges stating thatathe accused was found guilty ofacorruption crimes stipulated in article 3 of Law No. 20 of 2001 concerning amendments to Law No. 31 of 1999 concerning the Eradication of Corruption. As well as in handing down the verdict against the corruption of village funds in the verdict No. 52/Pid.Sus-TPK/2019/Pn.Mks, the panel of judges used juridical and sociological considerations. However, according to the author should judge using philosophical considerations.